A development of the training curriculum for learning design to promote sexuality education awareness for students of teachers at the high school level - Nanthawong, Nipitpon; Saokham, Artid (Asian Journal of Education and Training, 2023)
The purpose of this research aimed to study develop a curriculum and evaluate the effectiveness of a curriculum for learning design promoting sexuality education awareness. The sample used in the research consisted of 8 high school teachers from 8 subject groups in semester 1 of the academic year 2022 at Kowit Thamrong School, Chiang Mai. The research tools consisted of courses and user manuals, as well as a teacher competency assessment form and Satisfaction Survey Form. The data were analyzed by finding the mean and standard deviation. Together with the content analysis, Analysis data by Descriptive statistics and Content Analysis. The research results were found as follows; 1. The training curriculum development model to promote teachers' awareness of sexuality education consisted of 4 components: (1) curriculum principles, (2) objectives, (3) curriculum development process, and (4) measurement and evaluation. 2. During the curriculum assessment, it was established that educators had a dual focus. Firstly, they concentrated on facilitating learning methods that highlighted effective educational approaches (2.1). Secondly, they required a learning design that emphasized observation (2.2). This approach aligns with an educational model wherein curriculum development nurtures learners to comprehend the model in terms of perspective and efficiency.